Case Reports: Bronchial Mucosal Vasculature Is Also Involved in the Acute Vascular Distress Syndrome of COVID-19 - Jounieaux, Vincent; Basille, Damien; Toublanc, Bénédicte; Andrejak, Claire; Rodenstein, Daniel Oscar; Mahjoub, Yazine (Frontiers in Medicine, 2021)
Background: SARS-CoV-2 virus which targets the pulmonary vasculature is supposed to induce an intrapulmonary right to left shunt with an increased pulmonary blood flow. We report here what may be, to the best of our knowledge, the first videoendoscopic descriptions of an hypervascularisation of the bronchial mucosa in two patients hospitalized for Covid-19 pneumonia. Cases presentation: Two patients, 27 and 37-year-old, were addressed to our Pneumology department for suspicion of Covid-19 pneumonia. Their symptoms (fever, dry cough and dyspnoea) associated to pulmonary ground glass opacities on thoracic CT were highly suggestive of a Covid-19 disease despite repeated negative pharyngeal swabs RT-PCR. In both patients, bronchoscopy examination using white light was unremarkable but NBI bronchoscopy revealed a diffuse hypervascularisation of the mucosa from the trachea to the sub-segmental bronchi, associated with dilated submucosal vessels. RT-PCR performed in bronchoalveolar lavage (BAL) confirmed the presence of Sars-CoV-2. Conclusions: These two case reports highlight the crucial importance of the vascular component of the viral disease. We suggest that such bronchial hypervascularisation with dilated vessels contributes, at least in part, to the intrapulmonary right to left shunt that characterized the Covid-19 related Acute Vascular Distress Syndrome (AVDS). More, in this context, any observation of a diffuse bronchial hypervascularisation through NBI bronchovideoscopy dictates to perform a BAL for Sars-CoV-2 RT-PCR.